2017
DOI: 10.1111/jopy.12322
|View full text |Cite
|
Sign up to set email alerts
|

Too much of a good thing? Exploring the inverted‐U relationship between self‐control and happiness

Abstract: Our main finding is that self-control enhances subjective well-being with little to no apparent downside of too much self-control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
72
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 63 publications
11
72
0
2
Order By: Relevance
“…Moreover, we found that average moment-to-moment autonomous motivation accounted for some of the documented relation between self-control and well-being (Hofmann et al, 2014;Wiese et al, 2017), and extended the scope of that relation to include burnout and purpose.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, we found that average moment-to-moment autonomous motivation accounted for some of the documented relation between self-control and well-being (Hofmann et al, 2014;Wiese et al, 2017), and extended the scope of that relation to include burnout and purpose.…”
Section: Discussionsupporting
confidence: 58%
“…Despite having effects on the focal outcome, that is, whether people show goal-consistent behavior or not, selfregulatory strategies may also vary with regard to their effects on the person's well-being. Generally, self-control is positively related to well-being, and likely so because people with higher self-control experience less conflicts between their current desires and their goals (Hofmann et al, 2014;Wiese et al, 2017). Another possible path through which self-control may lead to higher well-being is through its positive effect on goal progress (Brunstein, 1993).…”
Section: Response Modulation Strategy Suppressing the Impulse To Quitmentioning
confidence: 99%
“…Despite having effects on the focal outcome, that is, whether people show goal-consistent behavior or not, self-regulatory strategies may also vary with regard to their effects on the person´s well-being. Generally, self-control is positively related to well-being, and likely so because people with higher self-control experience less conflicts between their current desires and their goals (Hofmann et al,2014;Wiese et al, 2017). Another possible path through which self-control may lead to higher well-being is through its positive effect on goal progress (Brunstein, 1993).…”
Section: Focusing On Negative Consequencesmentioning
confidence: 99%